Advances in Wireless Sensor Networks 7th China Conference, CWSN 2013, Qingdao, China, October 17-19, 2013. Revised Selected Papers - Sun, Limin; Ma, Huadong; Hong, Feng (Communications in Computer and Information Science, 2014)
This book constitutes the refereed proceedings of the 7th China Conference of Wireless Sensor Networks, held in Qingdao, China, in October 2013. The 35 revised full papers were carefully reviewed and selected from 191 submissions. The papers cover a wide range of topics in the wireless sensor network fields like node systems, infrastructures, communication protocols, data management.